Lock-in thermal test with corrected optical stimulation. Issue 4 (8th August 2022) - Ramos Silva, António; Vaz, Mário; Leite, Sofia; Gabriel, Joaquim
ABSTRACT: Among the Non-Destructive Testing (NDT) techniques available today, Active Infrared Thermal Testing (AIRTT) is certainly one of the most flexible and promising. The goal of this work was to compare the results obtained with a common Lock-in Thermal Test (LTT) and the same test using a true sinusoidal stimulation obtained through a closed-loop controller. The results showed a poor dynamic response of the common system and a lack of proportionality between the reference signal and the generated optical stimulation. To improve its response, it was implemented a PID controller using a light sensor to close the feedback loop. The amplitude images obtained with this controller showed a significant improvement in the results. Defects invisible with the common LTT were now identifiable. The phase images obtained using the controller with feedback revealed higher sensitivity with lower noise. Despite only one system was tested, the results show that the optical stimulation used in LTT is not very accurate and can/should be improved and, that a sensitivity 2.5 times higher than the common LTT was achieved with a real sinusoidal stimulation. Abbreviation: NDT: Non-Destructive Tests; AIRTT: Active Infrared Thermal Testing; LTT: Lock-in Thermal Test; cLTT: common LTT; PID: Proportional, Integral and Derivative; CFRP: Carbon Fibre Reinforced Polymers; TTT: Transient Thermal Tests; LDR: light-dependent resistor; PMMA: Poly(methyl methacrylate)